Pengaruh Edukasi Media Kartun Terhadap Peningkatan Pengetahuan Ibu dan Status Gizi Anak - Suprapto Suprapto (LPPM STIKES Guna Bangsa, 2022)
The study was to analyze the effect of cartoon media education on increasing mother's knowledge and child's nutritional status. The research design used was a quasi-experiment with a pretest and posttest design. The population was 32 Mather’ and children aged 1-5 years who visited the Barombong Health Center in Makassar. The sampling technique used was consecutive sampling with inclusion criteria. Mothers with children aged 1-5 years and mothers willing to participate in the entire research. The dependent variable of the study was maternal knowledge and child's nutritional status, while the treatment or the independent variable was cartoon media education. The variables in this study were the dependent mother's knowledge, and the independent variable was cartoon media education with pretest and posttest treatment. Instruments in the survey used cartoon media, questionnaire sheets, examinations, and interviews. The analysis used is a dependent T-test using the Wilcoxon test. The results show that the average value of knowledge before education is 14.69; in the measurement after education, the average value is 17.94. The statistical test value is 0.000<0.05, so it can be concluded that there is a difference between knowledge of PreTest and Post Test, so it can also be concluded that is an effect of education using cartoon media on mothers’ knowledge about child nutrition. That there is an effect of education using cartoon media on mothers' knowledge about nutrition. It's recommended that parents of children under five are encouraged to increase knowledge about nutritional status through education and collaboration with health workers.